Visceral leishmaniasis and HIV infection: the diagnostic and therapeutic problems. - Rocha, P S; Rebocho, L; Alvoeiro, L; Lourenço, G; Branco, R; Victorino, R M; de Moura, M C (Acta Médica Portuguesa, 1993)
We present the case of an HIV-seropositive drug addict patient whose seropositivity was unknown until admission to hospital, where he presented with a clinical picture of fever splenomegaly and weight loss. A diagnosis of visceral leishmaniasis was established. We stress the diagnostic difficulties well expressed in the need to repeat the bone marrow aspirate to detect the presence of leishmanias. The lack of response to conventional antimonial therapy is discussed as well as the role of pentamidine as an alternative therapy.